Diabetic encephalopathy: the role of oxidative stress and inflammation in type 2 diabetes - Reis, Flávio (2012)
Type 2 diabetes mellitus (T2DM) is a heterogeneous metabolic disorder associated with an increased risk for central nervous system disorders. Diabetic encephalopathy is a relatively unknown diabetes complication, characterized by electrophysiological, structural, neurochemical, and degenerative neuronal changes that lead to cognitive functioning limitations. Besides chronic hyperglycemia and dyslipidemia, diabetic encephalopathy represents the most relevant risk factor for cognitive dysfunction, increased incidence of dementia, and consequently Alzheimer´s disease (AD), also referred to as “type 3 diabetes.” There has been recent evidence suggesting that oxidative stress and inflammation are key pathogenic factors for T2DM, cognitive decline, and neurodegenerative diseases, including AD. Thus in this review we aim to ascertain brain mechanisms underlying the link between T2DM and AD with a focus on oxidative stress and inflammatory processes. We also intend to review the main antioxidant/anti-inflammatory therapeutic strategies targeting the brain and contributing to halt the progression from diabetic encephalopathy into AD.